Tabletit historian opetuksessa : opetuskokeilu Voionmaan lukiossa - Tuhkala, Ari (2013)
The research is a case study in Voionmaa gymnasiums history class. The aim of the study was test tablet computers in history course. The study was observed and the feedback from students was collected using questionnaire.